2009
DOI: 10.1371/journal.pgen.1000730
|View full text |Cite
|
Sign up to set email alerts
|

Forty-Three Loci Associated with Plasma Lipoprotein Size, Concentration, and Cholesterol Content in Genome-Wide Analysis

Abstract: While conventional LDL-C, HDL-C, and triglyceride measurements reflect aggregate properties of plasma lipoprotein fractions, NMR-based measurements more accurately reflect lipoprotein particle concentrations according to class (LDL, HDL, and VLDL) and particle size (small, medium, and large). The concentrations of these lipoprotein sub-fractions may be related to risk of cardiovascular disease and related metabolic disorders. We performed a genome-wide association study of 17 lipoprotein measures determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
296
5
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(336 citation statements)
references
References 38 publications
33
296
5
2
Order By: Relevance
“…Methodologies for quantifying HDL subpopulations (HDL 2 and HDL 3 ) and particle size (small, intermediate, and large) are only now becoming more accurate and available for larger study samples (such as NMR-based measurements). Two recent studies have examined specialized lipid phenotypes in thousands of subjects ( 123,229 ). One of these studies has investigated the signifi cant GWA loci with ApoA1, HDL 2 , HDL 3 , and HDL size among other specialized phenotypes ( 123 ).…”
Section: Family Studies In Investigation Of Private Variantsmentioning
confidence: 99%
“…Methodologies for quantifying HDL subpopulations (HDL 2 and HDL 3 ) and particle size (small, intermediate, and large) are only now becoming more accurate and available for larger study samples (such as NMR-based measurements). Two recent studies have examined specialized lipid phenotypes in thousands of subjects ( 123,229 ). One of these studies has investigated the signifi cant GWA loci with ApoA1, HDL 2 , HDL 3 , and HDL size among other specialized phenotypes ( 123 ).…”
Section: Family Studies In Investigation Of Private Variantsmentioning
confidence: 99%
“…We also analyzed a variant rs1367117, which has been reported to have POE on glucose level [6,42]. No significant association between the level of glucose from NMR metabolite panel and this variant was detected in our data.…”
Section: Resultsmentioning
confidence: 72%
“…In addition to the genome-wide analysis, we selected previously established associations from the study by Kettunen et al [9], where meta-analysis of 123 metabolites in 24,925 individuals revealed 62 associations with NMR metabolite levels, and tested if any of these associations show POEs. In total, five loci had p-values less than 0.05 (Supplementary Table 1), but none of them reached the threshold considered for significance after multiple testing correction (p corrected < 0.001).We also analyzed a variant rs1367117, which has been reported to have POE on glucose level [6,42]. No significant association between the level of glucose from NMR metabolite panel and this variant was detected in our data.…”
mentioning
confidence: 83%
“…Anyhow, the capacity of newer genetic loci of predicting future CV risk is estimated to be modest. Strong and reproducible results were reached in GWAS and other association studies related to lipid metabolism: GWAS have so far identified 43 loci involved with lipoprotein metabolism (131,132). For example, SNPs consistently associated to LDL levels were located in previously identified loci (ABCA1, APOA5-APOA4-APOC3-APOA1 and APOE-APOC clusters, APOB, CETP, GCKR, LDLR, LPL, LIPC, LIPG, and PCSK9) and new ones (CELSR2-PSRC1-SORT1) (133,134).…”
Section: Coronary Calciummentioning
confidence: 92%